(untitled) - Wells, Rosemary; Morton, Samantha; Rosemberg, Billy; Nelvana (Firm); Nickelodeon (Firm); Paramount Home Entertainment (Firm) (Hollywood, Calif., 2008)
Max & Ruby celebrates the warm and humorous relationship between Max, an enthusiastic and determined bunny, and his big sister Ruby.
Keywords: Max (Fictitious character : Wells); Ruby (Fictitious character : Wells); Drama; Friendship; Drama; Drama; Brothers and sisters; Drama; Juvenile films; Max (Fictitious character : Wells); Ruby (Fictitious character : Wells); Juvenile films; Juvenile films; Juvenile films; Friendship; Brothers and sisters; Television serials; Family; Animation; Television series; Fantasy television programs; Animated television programs; Animation; Adventure television programs; Childrens; Television series; Television programs; Animated television programs; Fantasy television programs; Adventure television programs; Television programs for children; Fantasy; Animation; Television series; Adventure; Animation; Television series; Television programs for the hearing impaired